Biogenesis of Hydrogen Sulfide and Thioethers by Cystathionine Beta-Synthase - Majtan, Tomas; Krijt, Jakub; Sokolová, Jitka; Křížková, Michaela; Ralat, Maria A; Kent, Jana; Gregory, Jesse F; Kožich, Viktor; Kraus, Jan P (Antioxidants & redox signaling, 2018)
AIMS: The transsulfuration pathway enzymes cystathionine beta-synthase (CBS) and cystathionine gamma-lyase are thought to be the major source of hydrogen sulfide (H2S). In this study, we assessed the role of CBS in H2S biogenesis. RESULTS: We show that despite discouraging enzyme kinetics of alternative H2S-producing reactions utilizing cysteine compared with the canonical condensation of serine and homocysteine, our simulations of substrate competitions at biologically relevant conditions suggest that cysteine is able to partially compete with serine on CBS, thus leading to generation of appreciable amounts of H2S. The leading H2S-producing reaction is condensation of cysteine with homocysteine, while cysteine desulfuration plays a dominant role when cysteine is more abundant than serine and homocysteine is limited. We found that the serine-to-cysteine ratio is the main determinant of CBS H2S productivity. Abundance of cysteine over serine, for example, in plasma, allowed for up to 43% of CBS activity being responsible for H2S production, while excess of serine typical for intracellular levels effectively limited such activity to less than 1.5%. CBS also produced lanthionine from serine and cysteine and a third of lanthionine coming from condensation of two cysteines contributed to the H2S pool. INNOVATION: Our study characterizes the H2S-producing potential of CBS under biologically relevant conditions and highlights the serine-to-cysteine ratio as the main determinant of H2S production by CBS in vivo. CONCLUSION: Our data clarify the function of CBS in H2S biogenesis and the role of thioethers as surrogate H2S markers. Antioxid. Redox Signal. 28, 311-323.
Keywords: kinetika; cystathionin-beta-synthasa; Animals; Sulfides; Catalysis; cystein; sulfidy; Kinetics; biologické markery; alternative reactions; Biomarkers; katalýza; sulfan; Mice, Knockout; myši knockoutované; síra; serin; animal model; Mice; sulfur metabolism; Cystathionine beta-Synthase; myši; Haplorhini; homocystein; Hydrogen Sulfide; Haplorrhini; Cysteine; enzyme kinetics; Serine; Homocysteine; zvířata; alanin; homocystinuria; Alanine; Sulfur